(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Figuring out fetal coronary heart can be essential for monitoring the situation of a fetus. While an ECG signal is recorded by way of putting electrodes on the maternal stomach, the fetal ECG is regularly masked by using the maternal ECG sign and noise. Via using an LMS adaptive filter to extract the fetal ECG signal, after which the use of the Pan & Tompkins algorithm to hit upon the QRS complexes, the fetal heart may be determined with very low errors.